Frequency of depression and its severity among family caregivers of cancer patients - Riaz, Irum; Kareem, Owais (Biological and Clinical Sciences Research Journal, 2025)
Family caregivers of patients with cancer experience substantial psychological burden, with depression being one of the most frequently reported mental health outcomes. Evidence from low- and middle-income countries remains limited, and context-specific data are needed to guide screening and supportive care strategies in oncology settings in Pakistan. Objective: To determine the frequency and severity of depression among family caregivers of patients with cancer and to examine its association with selected socio-demographic and caregiving-related factors at a tertiary care hospital in Pakistan. Methods: This descriptive cross-sectional study was conducted in the Department of Psychiatry, Nishtar Hospital, Multan, over six monthsfrom May 2024 to October 2024. A total of 196 family caregivers of patients with a confirmed diagnosis of cancer were enrolled using non-probability consecutive sampling. Depression was assessed using the depression subscale of the Hospital Anxiety and Depression Scale (HADS-D). A cut-off score of >8 was used to define the presence of depression, and severity was categorized as mild, moderate, or severe. Socio-demographic variables and caregiving characteristics were recorded using a structured proforma. Data were analysed using SPSS version 23. Associations between depression and explanatory variables were examined using chi-square tests, with p ≤ 0.05 considered statistically significant. Results: The mean age of caregivers was 38.6 ± 9.1 years, and 56.1% were female. Overall, 55.1% of caregivers screened positive for depression. Among those with depression, 44.4% had mild, 36.1% had moderate, and 19.4% had severe depressive symptoms. Depression was significantly more prevalent among female caregivers, those residing in rural areas, and caregivers from low and lower-middle socioeconomic groups. Higher depression severity was associated with longer duration of the patient’s illness. Lower educational attainment was also linked to a higher prevalence of depression, while caregiver age showed no significant association. Conclusion: Depression is highly prevalent among family caregivers of patients with cancer in this tertiary care setting in Pakistan, with a substantial proportion experiencing moderate to severe symptoms. Female gender, rural residence, lower socioeconomic status, lower educational level, and longer caregiving duration were associated with higher depressive burden. Routine psychological screening of caregivers and the integration of structured psychosocial support within oncology services may help mitigate caregiver distress and improve the overall quality of cancer care.